HYDROLOGICAL CONDITIONS IN THE INSHORE REGION OF KARWAR DURING 1965-1967 - Annigeri, C G (Indian Journal of Fisheries, 2011)
Studies on the hydrological conditions off Karwar were undertaken on board one of the vessels of I.N.P. during the years 1965 to 1967. The inshore samples collected from surface, 10 m and bottom (15-31 m), showed quite distinct demarlcation in the distribution of physico-chemical properties. The average monthly values of pH fluctuated between 8.0 and 8.4. Dissolved oxygen reached its maximum in the sub-surface layers. Saturation and supersaturation values were frequently observed at 10 m and 15-31 m than that at surface, indicating the zone of maximum photosynthesis below the surface waters. The distribution of nutrient salts showed that they are concentrated at bottom